Chromosomal DNA damage measured using the cytokinesis‐block micronucleus cytome assay is significantly associated with cognitive impairment in South Australians. (6th August 2014) - Lee, Sau Lai; Thomas, Philip; Hecker, Jane; Faunt, Jeffrey; Fenech, Michael
<x xml:space="preserve">Abstract</x> Loss of genome integrity may be associated with increased risk for neurodegenerative disease. The aim of this study was to investigate whether mild cognitive impairment (MCI) or Alzheimer's disease (AD) individuals have increased DNA damage relative to age‐ and gender‐ matched controls using the cytokinesis‐block micronucleus cytome (CBMN‐Cyt) assay. DNA damage was measured as micronuclei (MN), nucleoplasmic bridges (NPB), and nuclear buds (NBUD) in binucleated cells. The assay was performed on blood samples from 80 participants consisting of (i) MCI cases (N = 20) and age‐ and gender‐ matched controls (N = 20), and (ii) AD cases (N = 20) and age‐ and gender‐ matched controls (N = 20). There was a significant increase in MCI NBUD frequency (P = 0.006) relative to controls, which was also observed in male (P = 0.03) and female (P = 0.04) subgroups. For AD cases, there were no significant differences in assay biomarkers relative to controls. There was a significant negative correlation between Mini Mental State Examination (MMSE) and (i) MN in all controls, (R = −0.3, P = 0.04), and AD cases (R = −0.4, P = 0.03), (ii) NPB in all controls, (R = −0.4, P = 0.006) and AD cases (R = −0.5, P = 0.01), and (iii) NBUD in MCI cases (R = −0.5, P = 0.007) and AD cases (R = −0.7, P = 0.0002). The results suggest that an increase in lymphocyte CBMN‐Cyt DNA damage biomarkers may be associated with cognitive decline. Environ. Mol. Mutagen. 56:32–40, 2015. © 2014 Wiley Periodicals, Inc.